Collaboration of Pentahelix in Community-Based Stunting Prevention Program in Tembelang District - Putri, Sephia Nurlista; Hardjati, Susi (Journal of Public Representative and Society Provision, 2025)
This article analyzes the policies implemented by the Tembelang Health Center to reduce stunting cases in Tembelang District, Jombang Regency. Through the analysis, it was found that the efforts implemented were by forming a Penta Helix collaboration involving five actors including academics, business, community, government, and media which were implemented in the "Beli Emas di Tembelang" program innovation policy. The purpose of this study was to analyze and describe how the Pentahelix collaboration policy reduced stunting in Tembelang District. The research method used was a qualitative method with a descriptive research type, data collection techniques through observation, interview, and documentation techniques. Based on the results of the study, it was found that the five Pentahelix actors involved in the collaboration had carried out their roles accordingto their respective fields. The implementation of the collaboration was considered to have been carried out well as evidenced by the implementation of the "Beli Emas di Tembelang" program policy having reduced stunting to 3.82% in 2024. The success of the program policy is certainly inseparable from the role and contribution of stakeholders in the Pentahelix collaboration.